THE INFLUENCE OF THE AGE ON THE PREVALENCE OF GINGIVAL RECESSION IN PATIENTS WITH PERIODONTITIS - P. Mazur; I. M. Suprunovych (Український стоматологічний альманах)
Gingival recession is a common clinical condition in the dental practice, which is characterized by the root surface exposure due to the apical displacement of the marginal gingival tissues. Since the teeth' root surfaces become open to the environment of the oral cavity, the consequences of gingival recession are a disturbance of aesthetics (mainly when they occur in the frontal area), the development of hypersensitivity root caries, and non-carious cervical lesions. Despite the numerous studies carried out, the exact mechanism of the development of gingival recession is not fully understood, and it is generally accepted that it has a multifactorial etiology. Gingival recession can occur directly due to an infectious and inflammatory process in the periodontal tissues, anatomical features, as a result of the effect of mechanical or iatrogenic factors on soft tissues, or their action in combination with each other. The prevalence of gingival recessions worldwide varies from 22 to 100% and mainly depends on age, the size of the studied population, diagnostic criteria, and statistical data processing methods.